Síndrome de Burnout: um estudo de caso sobre as condições de trabalho e saúde com os professores da Escola Municipal São Francisco de Assis no município de Parintins - Queiroz, Judite Cidade de (Brasil, 2024)
Addressing the syndrome of physical and mental exhaustion in teachers is an important reality that must be debated in society and the scientific community, as the world of work and its dynamics have significantly impacted the field of workers' mental health. This study aimed to analyze working conditions, as well as their effects on the mental health of teachers belonging to the teaching staff of Escola Municipal São Francisco de Assis, located in Parintins, Amazonas. For this, the method of historical-dialectical materialism was used, based on bibliographical and field research, involving semi-structured interviews. In this way, it was possible to reveal that teachers experience great mental and physical exhaustion, due to overload in the work environment. It is important to bring to light the working conditions of teachers related to the neoliberal system, where the teacher as a worker is not valued, but rather their efficiency and productivity in the educational market. However, it is hoped that this study can contribute to the literature and subsequent research involving the topic addressed.